Estudos sobre as interações das proteínas seminais com as células espermáticas e componentes dos diluidores usados na criopreservação do sêmen e sobre marcadores moleculares de parâmetros do sêmen em animais de produção - Menezes, Erika da Silva Bezerra de (2014)
The objectives of this study were: 1) to evaluate aspects of interaction between goat seminal plasma proteins and milk proteins; 2) to determine if homolog Binder of Sperm Proteins (BSP) from stallion, boar and ram seminal share the binding properties of the bovine BSP for the milk proteins; the mechanism of bovine sperm protection by milk is similar in different species of mammals; 3) to investigate the interactions of BSP proteins present in goat seminal plasma and phospholipids from soybean lecithin-based extender; 4) to identify seminal plasma proteins associated with scrotal circumference and sperm parameters. Heated skimmed milk was incubated with goat seminal plasma proteins and loaded onto Sepharose CL-4B column both in the presence and absence of calcium. Fractions were eluted and evaluated by Western blots using anti-goat BSP antibodies. Also, we fractionated milk into two fractions, MF-1 (mostly whey proteins) and MF-2 (mostly caseins), which were incubated with goat seminal plasma proteins and passed through gel filtration columns. Eluted fractions were then analysed by immunoblotting with anti-BSP antibodies. In addition, a series of analysis was conducted to evaluate binding properties involving milk and seminal plasma proteins. In the first procedure, an ELISA plate was saturated with heated skimmed milk and then incubated with serial dilutions of purified BSP proteins, goat seminal plasma proteins and anti-goat BSP. In a second analysis, heated skimmed milk, casein, α-lactalbumin and β-lactoglobulin were spotted onto a nitrocellulose membrane with serial dilutions. Membranes were then overlaid with goat seminal plasma proteins. Binding between milk and seminal plasma components were detected by successive incubations with primary and secondary antibodies. A third set of analysis was conducted to evaluate interactions among ejaculated and caudal epididymal sperm, milk and goat seminal plasma proteins. Epididymal sperm from each animal was incubated with: (1) citrate-glucose medium followed by seminal plasma; (2) with seminal plasma followed by milk extender; (3) with milk extender followed by seminal plasma (Fig. 1). Both ejaculated and epididymal goat sperm were also incubated with citrate-glucose medium without seminal plasma, as positive and negative controls, respectively. Following incubations, sperm membrane proteins were extracted and the presence of goat BSP proteins was assessed by Western blot Furthermore, heated skim milk was incubated with seminal plasma proteins from bulls, stallions, boars and rams and then loaded onto gel filtration column. The proteins were eluted and fractions were analysed by immunoblotting. Moreover, the interaction of hospholipids vesicles from soybean lecithin-based extender (Andromed® and Bioxcell®) and goat BSP proteins was investigated by gel filtration chromatography and ultracentrifugation analysis. An appropriate volume of soybean-based extender was incubated with goat seminal plasma proteins and passed through a gel filtration column. Proteins were eluted and fractions analysed by Western blot. Ultracentrifugation analysis was performed in the absence or in the presence of phospholipid vesicles. These vesicles were isolated from soybean lecithin extender and incubated with goat seminal proteins. The presence of goat BSP proteins in the supernatant and in the pellet was assessed by Western blot. In addition, seminal samples from ten Curraleiro Bulls were subjected to 2-D electrophoresis and Coomassie blue-stained gels analyzed with PDQuest software. Our results demonstrated that goat BSP proteins bound to milk protein, specially caseins and β-lactoglobulin. In addition, these proteins interact with phospholipids vesicles of Andromed® and Bioxcell®. Bull, stallion and boar BSP proteins also bind to milk protein, whereas ram BSP proteins did not bind. Also, we identified that twenty and seven protein spots presented significant correlation with at least one reproductive parameter. In summary, our results indicate that goat BSP proteins bind to milk proteins and phospholipids from Andromed® and Bioxcell® semen extender. This suggests that these components play a significant role in protecting goat sperm by sequestrating all BSP proteins in semen. We also demonstrated that BSP homologs in boar, stallion seminal plasma share the binding properties of the bovine BSP for the milk proteins. Additionally, Curraleiro seminal plasma has potential proteins related to quality sperm parameters and they should be tested as putative fertility markers. These findings are of considerable interest in view of the mechanisms of sperm protection by extender constituents, for the development of novel extender free of animal components and the identification of proteins as potential biomarkers of fertility in bovine seminal plasma.